1994
DOI: 10.3892/ijo.5.2.189
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Ras Gene-Mutations and HPV in Lesions of the Human Female Reproductive-Tract

Abstract: Abstract. Compatible with the epidemiology and natural history of cervical cancer and with experimental findings that HPV-immortalized nontumorigenic cells are similar to cervical carcinoma cells, in terms of the quantity and type of viral RNA expressed, it is believed that additional cellular genetic events are necessary for tumorigenic conversion. In the current study we detected codon 12 point mutations of the K-ras oncogene with an incidence of 28.2% in malignant lesions of the cervix, as well as HPV 18 at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
1
7

Year Published

1995
1995
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 20 publications
0
14
1
7
Order By: Relevance
“…Although in several studies point mutations at codon 12 of the H-ras gene in endometrial carcinomas have not been frequently detected [23], the present study revealed such point mutations in 7.3% of cases, while in a previous study of ours 14% was detected [24],…”
Section: Discussioncontrasting
confidence: 48%
“…Although in several studies point mutations at codon 12 of the H-ras gene in endometrial carcinomas have not been frequently detected [23], the present study revealed such point mutations in 7.3% of cases, while in a previous study of ours 14% was detected [24],…”
Section: Discussioncontrasting
confidence: 48%
“…HPV status was determined by PCR using general primers GP5-GP6 (Snijders et al, 1990) as well as primers specific for HPV11, HPV16, HPV18 and HPV33 (Arends et al, 1991). PCR reaction conditions have been described (Koffa et al, 1994).…”
Section: Cells and Tissuementioning
confidence: 99%
“…The oligonucleotides used for K-ras, H-ras and N-ras codon 12 have been previously described [27][28][29]. Taq polymerase was purchased form Gibco BRL.…”
Section: Oligonucleotide Primers and Pcr Amplificationmentioning
confidence: 99%